Influence of Donor and Recipient CYP3A4, CYP3A5, and ABCB1 Genotypes on Clinical Outcomes and Nephrotoxicity in Liver Transplant Recipients. Issue 10 (October 2016) - Debette-Gratien, Marilyne; Woillard, Jean-Baptiste; Picard, Nicolas; Sebagh, Mylène; Loustaud-Ratti, Véronique; Sautereau, Denis; Samuel, Didier; Marquet, Pierre
Abstract : Background: This study investigated the influence of the CYP3A4*22, CYP3A5*3, and ABCB1 exons 12, 21, and 26 polymorphisms in donors and recipients on clinical outcomes and renal function in 170 liver transplant patients on cyclosporin A (CsA) or tacrolimus (Tac). Methods: Allelic discrimination assays were used for genotyping. Multivariate time-dependent Cox proportional hazard models, multiple linear regression using the generalized estimating equation and linear mixed-effect models were used for statistical analysis. Results: Expression of CYP3A5 by either or both the donor and the recipient was significantly associated with lower Tac, but not CsA, dose-normalized trough levels. In the whole population, graft loss was only significantly associated with longer exposure to high calcineurin inhibitor (CNI) concentrations (hazard ratio, 6.93; 95% confidence interval, 2.13-22.55), P = 0.00129), whereas in the Tac subgroup, the risk of graft loss was significantly higher in recipient CYP3A5*1 expressers (hazard ratio, 3.39; 95% confidence interval, 1.52-7.58; P = 0.0028). Renal function was significantly associated with: (1) baseline modification of diet in renal disease (β = 0.51 ± 0.05; P < 0.0001); (2) duration of patient follow-up (per visit, β = −0.98 ± 0.22; P < 0.0001); and (3) CNI exposure (per quantile increase, β = −2.42 ± 0.59; P < 0.0001). No genetic factor was associated with patient survival, acute rejection, liver function test results, recurrence of viral or other initial liver disease, or renal function. Conclusions: This study confirms the effect of CYP3A5*3 on tacrolimus dose requirement in liver transplantation and shows unexpected associations between the type of, and exposure to, CNI and either chronic rejection or graft loss. None of the genetic polymorphisms studied had a noticeable impact on renal function degradation at 10 years. Abstract : CsA and Tac bioavailability may be due in part to polymorphisms in the genes encoding the metabolizing enzymes CYP3A4, CYP3A5 and ABCB1. The authors confirm that CYP3A5*3 donor and recipient genotypes are relevant for CNI dosing in liver transplantation while none of the polymorphisms had an impact on long-term renal function. Supplemental digital content is available in the text.